Synthesis of an oxytetracyline-tolidin-BSA immunogen and antibodies production of anti-oxytetracyline developed for oxytetracyline residue detection with enzyme-linked immunosorbent assays technique - R, Widiastuti; TB, Murdiati; D, Riandari (Indonesian Animal Sciences Society, 2013)
An oxytetracycline-tolidin-bovine serum albumin (OTC-tolidin-BSA)-conjugate was synthezed as immunogen for producing specific antibodies in immunized rabbits that would be used as reagent for development of OTC residue detection with enzym-linked immunoassays technique. The immunogen was prepared through diazotization tolidin and subsequently reacted with OTC. The red purple immunogen of OTC-tolidin-BSA absorbed at wave lengths of 277 nm and 488 nm under UV screening absorbances and confirmation with the high performance liquid chromatography (HPLC) showed the absence of peak at retention time of 3.46 minutes. Characaterized result with SDS-PAGE showed the molecular weight of the OTC-tolidin-BSA at 69.79 kDA. Subsequently, the immunogen was immunized into New Zealand rabbits in order to produce the polyclonal antibodies. The antibodies were purified using a protein A sepharose column. The OD optimum responses of 0.92 to 1.20 were obtained from the second fractionation at dilution of 1/1000 by titrating the antibodies and OTC-tolidin-BSA coating antigen at concentration of 10 Âµg/mL on several bleeding times. Key Words: Oxytetracycline, OTC-Tolidin-BSA, Immunogen, Immunization, Antibodies